Integration of pathway structure information into a reweighted partial Cox regression approach for survival analysis on high-dimensional gene expression data1. Issue 7 (16th July 2015) - Liu, Wei; Wang, Qiuyu; Zhao, Jianmei; Zhang, Chunlong; Liu, Yuejuan; Zhang, Jian; Bai, Xuefeng; Li, Xuecang; Feng, Houming; Liao, Mingzhi; Wang, Wei; Li, Chunquan
<x xml:space="preserve">Abstract</x> Accurately predicting the risk of cancer relapse or death is important for clinical utility.